2019
DOI: 10.1021/acsami.9b05577
|View full text |Cite
|
Sign up to set email alerts
|

Maximizing RNA Loading for Gene Silencing Using Porous Silicon Nanoparticles

Abstract: Gene silencing by RNA interference is a powerful technology with broad applications. However, this technology has been hampered by the instability of small interfering RNA (siRNA) molecules in physiological conditions and their inefficient delivery into the cytoplasm of target cells. Porous silicon nanoparticles have emerged as a potential delivery vehicle to overcome these limitationsbeing able to encapsulate RNA molecules within the porous matrix and protect them from degradation. Here, key variables were i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
54
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

5
0

Authors

Journals

citations
Cited by 30 publications
(54 citation statements)
references
References 46 publications
0
54
0
Order By: Relevance
“…Pivotal peaks were observed at both functionalization steps (Scheme S1, Supporting Information): 1) CO stretching vibrations at 1720 cm −1 confirmed the presence of carboxyl groups from undecylenic acid (UA‐pSiNPs) molecules, which were first reacted to freshly etched pSiNPs, and 2) peaks at 1650 and 1550 cm −1 from amide groups verified the successful attachment of PAMAM dendrimers to UA‐pSiNPs via carbodiimide crosslinking chemistry (Figure S1E, Supporting Information). Previous work done using PAMAM‐pSiNPs have demonstrated a siRNA loading efficiency of 74% and a sustained release profile over 72 h. [ 24 ] Furthermore, our previous work showed that exposure of naked siRNA to RNAse A resulted in complete degradation after 1 h at an RNAse A concentration of 0.01 ng mL −1 . At a tenfold higher concentration of RNAse A (0.1 ng mL −1 ), all siRNA loaded into PAMAM‐pSiNPs was recovered after enzyme incubation.…”
Section: Resultsmentioning
confidence: 92%
See 4 more Smart Citations
“…Pivotal peaks were observed at both functionalization steps (Scheme S1, Supporting Information): 1) CO stretching vibrations at 1720 cm −1 confirmed the presence of carboxyl groups from undecylenic acid (UA‐pSiNPs) molecules, which were first reacted to freshly etched pSiNPs, and 2) peaks at 1650 and 1550 cm −1 from amide groups verified the successful attachment of PAMAM dendrimers to UA‐pSiNPs via carbodiimide crosslinking chemistry (Figure S1E, Supporting Information). Previous work done using PAMAM‐pSiNPs have demonstrated a siRNA loading efficiency of 74% and a sustained release profile over 72 h. [ 24 ] Furthermore, our previous work showed that exposure of naked siRNA to RNAse A resulted in complete degradation after 1 h at an RNAse A concentration of 0.01 ng mL −1 . At a tenfold higher concentration of RNAse A (0.1 ng mL −1 ), all siRNA loaded into PAMAM‐pSiNPs was recovered after enzyme incubation.…”
Section: Resultsmentioning
confidence: 92%
“…We have previously demonstrated that PAMAM‐pSiNPs are a potent non‐viral gene delivery vector for the delivery of siRNA. [ 24 ] PAMAM‐pSiNPs have been shown to both load and protect siRNA molecules. Representation of the functionalization steps followed and physicochemical characterization can be found in the Supplementary Information (Scheme S1, Figure S1, Supporting Information).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations